If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(t + 4) = 36 Reorder the terms: -9(4 + t) = 36 (4 * -9 + t * -9) = 36 (-36 + -9t) = 36 Solving -36 + -9t = 36 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -9t = 36 + 36 Combine like terms: -36 + 36 = 0 0 + -9t = 36 + 36 -9t = 36 + 36 Combine like terms: 36 + 36 = 72 -9t = 72 Divide each side by '-9'. t = -8 Simplifying t = -8
| 27+3y-6=11y-9-2y | | D=175+-70t | | x+18+4x=-30-4x-33 | | 24y=14y-8 | | 4r^6+15r^3-25=0 | | 14q^2-33qb+18b^2=0 | | -3(x-1)+8(x-3)=6x+7+-5x | | 50a^4+60a^2-20=0 | | 5a^4+6a^2-2=0 | | -7r+3t-8s-5r+12s+14r+5s-11r= | | 2s^2-7s-4=0 | | (u-3)(u-3)=2u^2-15u+29 | | 15a^2+17a-42=0 | | (-5)2= | | -15a^2-17a+42=0 | | 2x(3+6)=15 | | 3/x+2-1/x=1/5x | | 2+13x+15x^2=0 | | 6(9)+3(3)-1= | | 45x^2+39x+6=0 | | 3(4)+2(2)-4= | | 4(16)+5(-4)-2= | | 4(16)+5(-4)-2= | | -4=4(-4*-4)+5(-4)-2 | | 4w^6x^9/z^6 | | 8n/11+2=10 | | w^8/w^-9 | | 56w^3-17w^2-3w=0 | | -4=4*16+5(-4)-2 | | x+11y=41 | | y+10=9/2(1-10) | | (7x^2+5x)(3x-1)=0 |